Tasche des Fluchtlings - Oeser, Adrian (Germany, 2017)
This film tells the stories of three young Afghan refugees working on the project "Bag Mohajer", Refugee Bag. With the help of a German designer they make bags out of the boats and life jackets that have washed up on the Isle of Lesbos. Pouring themselves into their work, these refugees produce bags that travel to places they themselves can't access.
Keywords: Documentary films